Pengaruh Prasarana Jalan terhadap Tingkat Keselamatan Pengguna Jalan di Jalan Desa Tarahan, Kecamatan Katibung, Kabupaten Lampung Selatan - Sanjaya, Ketut Raditia; Misdalena, Felly; Adrian, Qadhli Jafar (Universitas Batanghari Jambi, 2025)
Traffic safety is a condition to reduce the risk of accidents during traffic caused by drivers, vehicles and the environment. On the Tarahan road section there are no traffic signs and there are several road sections that do not have road markings or have faded. The importance of this study is to determine the level of safety on the Tarahan road section, Katibung District, South Lampung. The method used is the quantitative method and the survey method. The questionnaire for this study uses two tests, namely the validity test and the reliability test using SPSS software and has been declared valid and the data instrument can be trusted. The questionnaire to road users and the survey method are in the form of data on the speed of drivers and road infrastructure. The average speed obtained for Light Vehicles (KR) is 47.19 Km / Hour, Heavy Vehicles (KB) is 37.87 Km / Hour and Motorcycles (SM) is 44.64 Km / Hour. After distributing the questionnaire to 100 respondents, the Likert scale/level of importance of road infrastructure was 92.4% and can be seen in the score interpretation criteria, namely that drivers agree on the importance of road infrastructure for road safety.